The influence of entrepreneurship subject on studentsâ interest in entrepreneurship with hidden curriculum as the intervening variable - Kuncoro, Amin; Rusdianto, Hutomo (Dinamika Pendidikan, 2016)
Higher education is a place of knowledge transfer with the certain framework set by a trusted institution. Nevertheless, the concept of knowledge transfer was still limited to a qualitative or tentative which made the output was only the micro scale of the institution scope. It was not appropriate to the goal of learning process in a very broad sense, both qualitatively and quantitatively. The objective of the study was to know the influence of entrepreneurship subject on studentsâ interest in entrepreneurship Â at Institut Pesantren Mathaliul Falah (IPMAFA) Pati with hidden curriculum as the intervening variable. It used WarpsPls analysis to test the model directly and directly. The samples of the study were 30 Islamic banking students who got entrepreneurship subject and Islamic community development who did not get the entrepreneurship subject. The results of this study explained that the entrepreneurship subject influenced studentsâ interest in entrepreneurship and the second model test results showed that hidden curriculum was not able to become the intervening variable for studentsâ interest in entrepreneurshipPerguruan tinggi merupakan tempat transfer ilmu dengan kerangka yang telah ditetapkan oleh lembaga yang dipercaya. Namun demikian, konsep dari proses transfer ilmu masih sebatas kualitatif atau bahkan tentatif sehingga ouput yang dihasilkan masih berkutat pada skala mikro dari lingkup lembaga. Hal ini belum selaras dengan tujuan proses pembelajaran yang mempunyai arti sangat luas, baik kualitatif maupun kuantitatif. Penelitian ini bertujuan untuk mengetahui pengaruh mata kuliah kewirausahaan terhadap minat berwirausaha pada mahasiswa Institut Pesantren Mathaliul Falah (IPMAFA) Pati dengan hidden curriculum sebagai variabel intervening. Metode penelitian ini menggunakan analisis WarpsPls dengan menguji model langsung dan tidak langsung. Sampel yang diteliti adalah mahasiswa dengan Prodi Perbankan Syariah dan mahasiswa Prodi Pengembangan Masyarakat Islam dengan kriteria mahasiswa yang telah mendapatkan Matakuliah Kewirausahaan dan yang belum mendapatkan Matakuliah Kewirausahaan dengan jumlah sampel 30 orang. Hasil penelitian ini menjelaskan bahwa Matakuliah Kewirausahaan berpengaruh terhadap minat berwirausaha dan hasil uji model yang kedua menjelaskan bahwa hidden curriculum tidak mampu menjadi variabel intervening bagi minat berwirausaha mahasiswa.